Virtual Reality as a Medium For Worship Simulation: Effectiveness And Its Impact on The Spritual Reinforcement of Learners - Khairunnisa, Khairunnisa; Mohammad Djamil M.Nur; Darmansyah, Darmansyah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2025)
This article aims to analyze the effectiveness and challenges the use of AI hardware in PAI is. This study employs a qualitative descriptive method through literature review and documentation, analyzing various sources related to the implementation of AI in religious education. The research results show that AI can enhance student engagement and provide better learning. However, there are several issues: high costs, teachers who are not proficient in using AI, and the possibility of non-compliance with PAI standards. Therefore, the implementation of AI in PAI learning must be carried out with careful planning, appropriate policy support, and adequate training for teachers.